Potential antecedents and outcomes of frontline employees’ service recovery performance - Nik Mohd Masdek, Nik Rozana; Abdul Aziz, Yuhanis; Awang, Khairil Wahidin (Faculty of Economics and Management, Universiti Putra Malaysia, 2011)
Frontline employees frequently act as a bridge between a firm and its customers. Therefore, customers often form their opinions on service quality of the firm based on how well the frontline employees perform. This conceptual paper intends to explore some potential antecedents that might have an impact with particular regard to frontline employees’ service recovery performance. In addition, it also looks at its potential impact on selected outcomes. Using the existing literature, hypotheses are formulated to provide understanding of the relationships between service recovery performance antecedents and its associated outcomes. This would assist managers in identifying and managing the factors, and thus will contribute towards creating a loyal base of satisfied customers. Implications for managerial actions and future research avenues are discussed. Empirical support is obviously needed for the proposed conceptual framework and therefore it has been planned for it to be tested in a hotel environment. An important reason for the hotel industry to be chosen is because of the booming of the tourism industry where the hotel sector is seen as the biggest contributor.